Aircraft Electricity and Electronics, Sixth Edition - Eismin, Thomas K.; McGraw-Hill eBooks (New York, N.Y. : McGraw-Hill Education, 2014)
Fully updated for the latest technological advances, this comprehensive text describes design concepts, FAA certification requirements, and aerospace-quality maintenance and repair techniques for aircraft electrical and electronics systems. The materials contained in this book will benefit designers, engineers, and technicians for all aircraft and aerospace vehicles. The requirements for the FAA Airframe and Powerplant Mechanic certification are also presented.
REVIEW QUESTIONS -- 14. Radio Theory -- CHAPTER PRELIMINARIES -- RADIO WAVES -- AMPLIFIERS -- FUNCTIONS OF A TRANSMITTER -- RECEIVERS -- REVIEW QUESTIONS -- 15. Communication and Navigation Systems -- CHAPTER PRELIMINARIES -- COMMUNICATIONS -- NAVIGATION SYSTEMS -- INSTALLATION OF AVIONICS EQUIPMENT -- ANTENNAS -- REVIEW QUESTIONS -- 16. Weather Warning and Other Safety Systems -- CHAPTER PRELIMINARIES -- RADAR -- DIGITAL AIRBORNE WEATHER RADAR SYSTEMS -- RADAR MAINTENANCE -- LIGHTNING DETECTION -- AVIATION SATELLITE WEATHER -- GROUND PROXIMITY WARNING SYSTEMS -- TRAFFIC COLLISION AVOIDANCE SYSTEM (TCAS) -- REVIEW QUESTIONS -- 17. Instruments and Autoflight Systems -- CHAPTER PRELIMINARIES -- RPM-MEASURING INSTRUMENTS -- TEMPERATURE INDICATORS -- SYNCHRO SYSTEMS -- FUEL-QUANTITY INDICATORS -- ELECTROMECHANICAL FLIGHT INSTRUMENTS -- ELECTRONIC FLIGHT SYSTEMS -- AUTOMATIC FLIGHT CONTROL SYSTEMS -- TYPICAL AUTOMATIC PILOT AND FLIGHT CONTROL SYSTEM -- THE BOEING B-757 FLIGHT MANAGEMENT SYSTEM -- REVIEW QUESTIONS -- A. Appendix -- APPENDIX PRELIMINARIES -- USEFUL EQUATIONS -- ELECTRICAL AND ELECTRONIC SYMBOLS -- USEFUL ACRONYMS AND ABBREVIATIONS -- B. Glossary.
Includes bibliographical references and index.
Also available in print edition.
Electronic reproduction.
Mode of access: Internet via World Wide Web.
In English.
Description based on e-Publication PDF.
Keywords: Airplanes -- Electric equipment; Avionics; Airplanes -- Electronic equipment; Electronic books